Equivalence‐based instruction of academic skills: Application to adolescents with autism. Issue 2 (6th March 2018) - Stanley, Caleb R.; Belisle, Jordan; Dixon, Mark R.
Abstract : This study evaluated the efficacy of three equivalence‐based instruction procedures on the acquisition of novel academic skills by 3 adolescents diagnosed with autism in a school setting. The skills targeted for instruction were related to topics in history, science, and mathematics, and were taught using different training structures from the PEAK‐E curriculum. All participants demonstrated mastery of the trained relations and the tested derived relations following all variants of equivalence‐based instruction.